Changes in Lipid, Fatty Acid, α-Tocopherol and Phytosterol Content of New Zealand Undaria pinnatifida With the Time and Location - Boulom, Sayvisene (Auckland University of Technology, 2012)
Seasonal changes in the contents of lipids, fatty acids, phytosterol and α-tocopherol in the brown macroalgae Undaria pinnatifida were investigated in this research. The Undaria samples were collected monthly from June to December 2011 from mussel lines in the Marlborough Sounds. Lipids were measured on a dry weight (DW) basis. U. pinnatifida had a low lipid content which ranged from 17.07 to 45 mg/g dried weight (DW) in blade and between 20.70 and 63 mg/g in the sporophyll. In New Zealand, U. Pinnatifida is always present and growing in summer although its degradation was reported in summer in Japan due to high sea temperatures. The sea temperatures in the Marlborough Sounds (New Zealand) are cool in summer and are conducive for Undaria growth. The saponifiable lipid fraction was derivatised into fatty acid methyl esters (FAMEs) and analysed by gas chromatography flame ionised detector GC-FID to identify and quantify the individual fatty acids in U. pinnatifida. It was found that the level of SFAs increased from winter to summer. In December the most abundant SFA was palmitic acid (C16:0) which was up to 6.49 mg/g in the blade and the predominant MUFA was oleic acid (C18:1n-9c) with a highest level of, 3.40 mg/g, also in the blade. In December, U. pinnatifida was also found to be a richer source of PUFAs than the SFAs and MUFAs. These PUFAs consisted of both omega-6 (n-6 or ω-6) and omega-3 (n-3 or ω-3) PUFAs. The abundant n-6 PUFAs are C18:2n-6, C18:3n-6 and C20:4n-6 also reached a maximum in December. By contrast some of the PUFAs decreased in summer. C18:3n-3, C18:4n-3 and C20:5n-3 fatty acids were higher in winter. The New Zealand U. pinnatifida showed high concentrations of n-3 fatty acids and demonstrated a nutritionally balanced of omega-6 (n-6): omega-3 (n-3) ratio. The unsaponifiable lipid fractions examined contained two principal phytosterols; fucosterol and 24 methylenecholesterol, and the fat-soluble vitamin α-tocopherol. These non-saponifiable compounds were identified by high pressure liquid chromatography with UV/Vis detection (HLPC-UV) and gas chromatography mass spectrometry (GC-MS), followed by GC-FID analysis for quantitation. The unsaponifiable lipid content represented less than 1% of total lipids in U. pinnatifida. α-Tocopherol was the only fat-soluble vitamin identified in New Zealand Undaria. Fucosterol and 24 methylenecholesterol were found higher concentrations in the winter. The content of fucosterol ranged from 146 to 338 µg/g and 24 methylenecholesterol was between 8.4 and 48 µg/g. However, the content of α-tocopherol was relatively high in winter and spring (13 and 14 µg/g) and then slightly decreased in summer (9.6 µg/g). This study showed that U. pinnatifida from New Zealand can be a balanced source of fatty acids and additionally contained the useful antioxidant α-tocopherol.
Keywords: Fatty acid profiles; α-tocopherol and phytosterol; New Zealand Undaria pinnatifida